Diet Therapy and Physical Activity on Blood Sugar Levels in Diabetes Mellitus Patients in the Inpatient Room at Luwuk Banggai Regional Hospital - Inamah, Inamah; Sahalessy, Yona; Pannyiwi, Rahmat; Werdyaningsih, Endang; Yulis, Dian Meiliani (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Diabetes mellitus is a degenerative disease that is closely related to diet therapy. Diet Therapy is a description of the types, amount and composition of food a person eats every day. An urban lifestyle with a diet pattern that is excessively high in fat, salt and sugar results in various diseases including diabetes mellitus. The aim of the research is to determine the effect of diet therapy and physical activity on blood sugar levels in diabetes mellitus patients. This research is a quantitative research using an observational approach with a cross sectional design, namely research by studying the correlation between risk factors and the effects they cause by approaching, observing or collecting data at one time. The results of the statistical analysis test show the chi-square test X2 = 4.022 or at a confidence level (α = 0.05) P-value 0.045. So it can be concluded that there is a significant relationship between physical activity variables and blood sugar levels in diabetes mellitus patients. The Odd Ratio (OR) value = 3.3 (95% CI 0.090 – 1.002) meaning that less physical activity has a risk of developing Type II DM that is 3.3 times greater than those with less diet therapy.